A Study of Serum Zinc level in Cirrhosis of Liver (Bangladesh Journal of Medical Biochemistry, 2013)
Cirrhosis is a consequence of chronic liver diseases. Zinc is a micronutrient that plays an important role in the function of liver. This cross-sectional study was carried out in the Department of Biochemistry, Dhaka Medical College, from July 2010 to June 2011 to observe the association of serum zinc level with liver cirrhosis. A total of 100 adults, both males and females with age range of 18-60 years, of which 50 were healthy subjects and 50 adult hospitalised cirrhotic patients were selected purposively for the study according to selection crieteria. Fasting serum zinc level was measured with atomic absorption spectrophotometer. Serum zinc level was found to be low in 72% patients. Mean ±SD of serum zinc levels (?g/L) were 610.32 ± 169.60 and 827.66 ± 267.32 in cases and controls respectively. In cirrhotic patients serum zinc level was significantly lower than that of healthy controls (P